Persepsi Masyarakat Terhadap Manfaat Beternak Kuda di Kabupaten Jeneponto - Astati, Astati; Mursidin, Mursidin; Rusny, Rusny; Susanti, Handayani Indah; Hifizah, Amriana; Qurniawan, Anas (Anoa: Journal of Animal Husbandry, 2024)
Horse breeding can provide various benefits in improving welfare, both for individuals and society as a whole. Horses can mainly be utilized as a means of transportation and a source of labor pulling carts. This study aims to determine public perception of the benefits of horse farming. This research was conducted from June to July 2022 in North Tolo Village, Kelara District, Jeneponto Regency. This research is descriptive quantitative with survey methods. Simple random sampling of 55 horse breeders. The data obtained were analyzed descriptively with frequency distribution and measurements using the Likert scale (strongly disagree – strongly agree) to determine public perceptions of the benefits caused by raising horses. Based on the results of the analysis, this study shows that the public responds strongly agree to the benefits of raising horses to improving welfare, consumption purposes, and as a workforce.